The role and tasks of family nurse in the care of seniors in their place of residence - field study conducted among nursing staff in Gdańsk - Magdalena Lemska; Elżbieta Bernaciak; Wioletta Mędrzycka-Dąbrowska; Grażyna Mazurek; Magdalena Michalewicz; Helena Mirus-Arabik (Kazimierz Wielki University, 2019)
Demographic changes taking place in Poland and in the world, a decrease in the number of births and prolonged life expectancy have resulted in an increase in the number of elderly people. The success of today's medicine is among others prevention of chronic disease complications and skillful education of the patient at every level. Longer life expectancy and a quantitative increase in the phenomenon of disability, and above all a shortening of hospitalization and stays in inpatient medical facilities has resulted in moving the patient's treatment and care to the home environment, which is an optimal place of residence for the elderly. The family nurse and primary care physician are then the most important link in the care of elderly and their families. The provision of nursing services in the patient's place of residence is characterized by a unique specificity in other areas of nursing. Very often, as a result of the existing situation and possibilities, the nurse has to demonstrate not only professional knowledge and skills, but also flexibility, adaptability and creativity in dealing with a shortage of basic things, e.g. basic auxiliary equipment, access to the patient's bed, etc. The conducted field study shows selected scope of tasks performed by nursing staff in this respect on the example of patients in the city of Gdańsk.